SUDDEN DEATH OF A MIDDLE AGED MALE DUE TO PULMONARY TUBERCULOSIS EXAGGERATED BY MINOR TRAUMA (ASSAULT): A MEDICO-LEGAL CASE REPORT AND REVIEW OF THE LITERATURE - Kumar, Sanjay; Millo, Tabin; Gupta, Mohit; Yadav, Abhishek; Mittal, Anil Kumar (Journal of Forensic Medicine and Toxicology, 2017)
Tuberculosis is the prototype of the granulomatous inflammatory diseases, caused by Mycobacterium tuberculosis. Immune reactions are usually involved in the development of granulomas (referred to as a tubercle in this disease) often characterized by the presence of central caseous necrosis, rare in other granulomatous diseases. Although it is uncommon but when exaggerated by some trauma it may account for sudden death.